Intercultural Communication of EFL Students with Foreigners as a Strategy of Teaching Speaking - Syarifudin Syarifudin; Hery Rahmat (EDULANGUE, 2021)
This study aimed to explore the students' perceptions of intercultural communication with foreigners, their intercultural communication strategies with foreigners, and its implication toward their speaking ability. This descriptive qualitative study involved eight university students who had taken the Speaking class and individual speaking activity with foreign tourists. To collect the data, the researchers used video recording, interviews, and documents. The findings indicated that the students positively perceived incorporation of intercultural communication with foreigners. It was also unveiled that the students used various verbal communication strategies during their intercultural communication with foreigners. This study postulates that intercultural communication has positive implications on students' speaking abilities.